Prestasi belajar matematika dengan TGT dan NHT pada siswa bergaya belajar kinestetik - Ridam Dwi Laksono (Jurnal Pendidikan Edutama, 2020)
Abstract: With the implementation of K-13, it is necessary to innovate learning models on the material, tools and how to deliver them. The purpose of this study is to find out whether the mathematics learning with TGT and NHT models  that have been innovated according to the 2013 curriculum, whether students have the same learning achievement. Second, to find out the learning style as an internal factor of students, is there an influence on the achievements. Third, to find out the interaction between learning models and student learning styles on student achievement. This activity is carried out by means of quasi experiments. Student learning achievement as the dependent variable, learning models and learning styles as independent variables. Statistical analysis using two-way ANOVA. Student achievement data is taken using cognitive test instruments and classification of learning styles using learning style questionnaires. Obtained research results (1) student achievement on the TGT learning model is better than student achievement on the NHT learning model, (2) there is no influence of student learning styles on learning achievement, (3) there is an interaction between learning models with learning styles. Students with kinesthetic learning styles have higher achievement when learning with the TGT learning model, compared to students who have the same learning style on NHT learning. Keyword: TGT, NHT, Learning Style, Peer Learning. Abstrak: Dengan diberlakukanya K-13, perlu dilakukan inovasi model pembelajaran pada materi, perangkat dan cara penyampaiannya. Tujuan penelitian ini pertama untuk mengetahui apakah pembelajaran matematika dengan model TGT dan NHT yang telah diinovasi sesuai kurikulum 2013, siswanya memiliki prestasi hasil belajar yang sama. Kedua untuk mengetahui gaya belajar sebagai faktor internal siswa, apakah terdapat pengaruh terhadap prestasi yang dicapai. Ketiga untuk mengetahui interaksi antara model pembelajaran dengan gaya belajar siswa terhadap prestasi siswa. Kegiatan ini dilakukan dengan cara eksperimen kuasi. Prestasi belajar siswa  sebagai variabel terikat, model pembelajaran dan gaya belajar sebagai variabel bebas. Analisis statistik menggunakan ANOVA dua jalan. Data prestasi hasil belajar siswa diambil dengan menggunakan instrumen tes kognitif dan klasifikasi gaya belajar menggunakan angket gaya belajar. Diperoleh hasil penelitian (1) prestasi belajar siswa pada model pembelajaran TGT lebih baik dari pada prestasi belajar siswa pada model pembelajaran NHT, (2) tidak terdapat pengaruh gaya belajar siswa terhadap prestasi belajar, (3) terdapat interaksi antara model pembelajaran dengan gaya belajar.  Siswa dengan gaya belajar kinestetik, memiliki prestasi yang lebih tinggi saat belajar dengan model pembelajaran TGT, dibandingkan siswa yang memiliki gaya belajar yang sama pada pembelajaran NHT.   Kata kunci: TGT, NHT, Gaya Belajar, Pembelajaran teman sebaya.